The Impact of Leader-Member Exchange on General Self-Efficacy: Evidence from China - Cui, Xuanwei (PT FORMOSA CENDEKIA GLOBAL, 2024)
Extant research has witnessed an increasing interest in understanding antecedents and outcomes of General Self-Efficacy (GSE); however, academic studies have not yet explored the role of Leader-Member Exchange (LMX) in giving rise to GSE. By drawing on Social Comparative Theory, the current study aims to examine the impact of LMX on GSE. The current study used a cross-sectional research design with survey methodology. Data were collected from 114 students in three universities in the eastern region of China. The findings indicated that LMX did not predict GSE, β = - .12, t(112) = -1.26, p = .21. To conclude, the current study might be essential for building the basics for comprehending how LMX affects GSE among university students in the eastern region of China.